Quantification of peptides released during in vitro digestion of cooked meat. (15th April 2016) - Sayd, T.; Chambon, C.; Santé-Lhoutellier, V.
Highlights: Identification and quantification of the peptides by label free mass spectroscopy. Highest number of peptides identified in beef meat digests. Comprehensive database for meat protein digestion associated with cooking conditions. Abstract: We aimed to identify and quantify the peptides generated during in vitro digestion of cooked meat by liquid chromatography coupled with high resolution mass spectrometer. A total of 940 non-redundant peptides in the gastric compartment and 989 non-redundant peptides in the intestinal compartment were quantified and identified. Among the 71 different proteins identified, 43 meat proteins were found in the two digestive compartments, 20 proteins were specific to the gastric compartment and 8 proteins to the intestinal compartment. In terms of estimation, the proteins involved in muscle contraction and structure were preferentially enzymatically hydrolyzed in the small intestine. The effect of cooking provided different but less clear patterns of digestion. To the best of our knowledge, this constitutes the highest number of peptides identified in beef meat digests and provides a comprehensive database for meat protein digestion associated with cooking conditions. Such quantitative and qualitative differences may have important nutritional consequences.